Carbon and nutrients output by harvesting Acacia mearnsii De Wild to four years old at the central Depression, RS - Caldeira, Marcos Vinicius Winckler; Godinho, Tiago de Oliveira; Saidelles, Fabio Luiz Fleig; Viera, Márcio; Schumacher, Mauro Valdir; Castro, Kallil Chaves (Comunicata Scientiae, 2014)
The aim of this study was to estimate the content and export of carbon, macro and micronutrients inthe different components (leaf, alive and dead branch, bark, wood and roots) of the Acacia mearnsiitrees with 4 years old of age in Arroio dos Ratos-RS, in order to provide the forest management,based on the criterion of minimum export of nutrients. After determining the diameter distributionand its division into diameter classes (seven classes), three trees were selected in each classes. Usingthe 21 trees felled, the biomass of different components of trees was estimated. It was observed thatwood, which represents about 64% of the biomass, contains 50% of accumulated Ca, 21% N, 27% P,30% K, 37% Mg, 45% of S, 25% B, 37% Cu, 9% Fe, 26% Mg and 41% Zn. While the leaf, which represents3% of total biomass, contains 20; 18; 12; 5; 10; 10; 17; 18; 5; 19 and 6% N, P, K, Ca, Mg, S, B, Cu, Fe,Mg and Zn, respectively. The export of nutrients from the crops of A. mearnsii can be minimized withretention of crop residues on the soil removal only of wood and bark.